Median sacral artery anterior to the left common iliac vein: From anatomy to clinical applications. A report of two cases - Stoyan Kostov; Stanislav Slavchev; Deyan Dzhenkov; George Stoyanov; Nikolay Dimitrov; Angel Yordanov (Elsevier, 2021)
Background: The median sacral artery (lat. arteria sacralis mediana) [MSA] is a small vessel that arises from the dorsal aspect of the aorta just above its bifurcation. It passes through the presacral space and descends in the midline, anterior to the fourth and fifth lumbar vertebrae, sacrum and coccyx, and posterior to the common iliac vein or iliocaval junction. Case report: Herein we describe two cases of MSA running in front of the left common iliac vein. To the best of our knowledge, MSA passing anterior to the left common iliac vein has previously been reported only once.The risk of damaging the artery, when located anterior to the left common iliac vein is increased in gynecological procedures in the presacral region - sacrocolpopexy or sacrohysteropexy, presacral neurectomy, retroperitoneal presacral tumors resection, selective lymphadenectomy, and sentinel lymph node biopsy. Conclusions: Damaging the MSA can result in massive hemorrhage, especially when it is retracted into the sacral foramina.The MSA is regularly found during dissections in the presacral region, not only in gynecological procedures, but also during anterior lumbar spine, urologic and orthopedic surgeries.